Combined effect of copper and hydrodynamic conditions on Myriophyllum alterniflorum biomarkers. (May 2018) - Krayem, Maha; Deluchat, Véronique; Hourdin, Philippe; Fondanèche, Patrice; Lecavelier Des Etangs, Florence; Kazpard, Véronique; Moesch, Christian; Labrousse, Pascal
Abstract: The aim of this study is to determine the combined effect of copper and hydrodynamic conditions on the response of certain biomarkers of an aquatic macrophyte, namely Myriophyllum alterniflorum . Watermilfoil biomarkers are monitored in a synthetic medium enriched or not with copper (100 μg.L −1 ) for 21 days in aquarium systems (150 L), under three hydrodynamic conditions: laminar, turbulent, and calm. The studied biomarkers are: respiratory and photosynthetic activities; concentrations of chlorophyll a, b and carotenoids; osmotic potential; hydrogen peroxide content; and growth. In addition, Cu contents in water and in Myriophyllum alterniflorum (roots and shoots) are investigated. The hydrodynamic conditions only affect watermilfoil morphology. Copper accumulates less in turbulent zones; moreover, it is more likely to accumulate in shoots than in roots, except within the calm zone. Cu leads to: i) a significant increase in H2 O2 content, ii) a decrease in root growth, pigment content, osmotic potential, photosynthesis and respiration rates, and iii) an inhibition of shoot branching. Differential effects are also observed between younger and older parts, thus indicating the benefit of considering these two plant parts separately in water quality biomonitoring. Highlights: Several biomarkers could respond to copper exposure. Cu impacts the biochemical, physiological and morphological biomarkers. Hydrodynamic conditions affected watermilfoil morphology and copper accumulation. Copper effects were higher in old watermilfoil parts than young ones